Անդրադարձ Թէոդորոս Քռթենաւորի երկերի բառապաշարին - Համբարձումեան, Վազգէն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Седьмой век армянской духовной и церковной жизни породил нам многих известных деятелей, благодаря которым их эпоха была названа жемчужиной на короне армянской истории. Они представляли целую плеяду. Среди них был и Теодорос Кртенавор – церковный деятель со знаменитой родословной, учитель. Его церковно-богословские труды — ценный вклад в истории армянской словесности и лексики․ The seventh century of the Armenian spiritual and ecclesiastical life produced many famous people, thanks to whom their epoch was named as the crown pearl of the Armenian history. They represented a whole galaxy: one of them is Theodoros Krtenavor of noble origin, teacher of the pious. His ecclesiastical and theological works contribute valuably to the history of the Armenian lexicology.
Keywords: History; Literature